Prespliceosomal assembly on microinjected precursor mRNA takes place in nuclear speckles - Melcák, I; Melcáková, S; Kopský, V; Vecerová, J; Raska, I (Molecular biology of the cell, 2001)
Nuclear speckles (speckles) represent a distinct nuclear compartment within the interchromatin space and are enriched in splicing factors. They have been shown to serve neighboring active genes as a reservoir of these factors. In this study, we show that, in HeLa cells, the (pre)spliceosomal assembly on precursor mRNA (pre-mRNA) is associated with the speckles. For this purpose, we used microinjection of splicing competent and mutant adenovirus pre-mRNAs with differential splicing factor binding, which form different (pre)spliceosomal complexes and followed their sites of accumulation. Splicing competent pre-mRNAs are rapidly targeted into the speckles, but the targeting is temperature-dependent. The polypyrimidine tract sequence is required for targeting, but, in itself, is not sufficient. The downstream flanking sequences are particularly important for the targeting of the mutant pre-mRNAs into the speckles. In supportive experiments, the behavior of the speckles was followed after the microinjection of antisense deoxyoligoribonucleotides complementary to the specific domains of snRNAs. Under these latter conditions prespliceosomal complexes are formed on endogenous pre-mRNAs. We conclude that the (pre)spliceosomal complexes on microinjected pre-mRNA are formed inside the speckles. Their targeting into and accumulation in the speckles is a result of the cumulative loading of splicing factors to the pre-mRNA and the complexes formed give rise to the speckled pattern observed.
Keywords: antisense oligodeoxyribonukleotidy; Temperature; sestřih RNA; RNA, Messenger; RNA Splicing; mutace; mikroinjekce; prekurzory RNA; Spliceosomes; HeLa buňky; spliceozomy; Microinjections; RNA Precursors; lidé; HeLa Cells; Humans; Oligodeoxyribonucleotides, Antisense; teplota; struktury buněčného jádra; Mutation; Cell Nucleus Structures; messenger RNA